The Social Construction of Bughāt as a Technology of Abbasid Hegemony in al-Māwardī’s al-Aḥkām al-Sulṭāniyyah - Hikami, Abdullah Faqih; Fikri, Syarifuddin Ala Dzil (Yayasan Pesantren Mahasiswa An-Nur, 2025)
The Islamic law of rebellion (bughāt) is traditionally interpreted as a protective framework or a neutral theological derivation designed to regulate internal political conflicts. Challenging these static interpretations, this study employs a genealogical deconstruction synthesized with social constructionism and power/knowledge frameworks to investigate al-Māwardī’s al-Aḥkām al-Sulṭāniyyah as an artifact of imperial survival. Findings reveal that al-Māwardī’s formulation of bughāt functions as a sophisticated